English teachers' readiness in using computers as a teaching tool in language teaching among English secondary school teachers in Samarahan Division, Sarawak / Suzanne Abang Balla - Abang Balla, Suzanne (2015)
Teachers’ readiness in using computer and its technology as teaching tool in English Language teaching is sought in this study. The samples are 124 English secondary teachers and MUET teachers in Samarahan Division of Sarawak. There are three objectives for this study. Firstly, it is to find out how frequent do English Language actually used computer and its technology as teaching tool in their English teaching. Secondly, it is to find out the usage of computer and its technology as teaching tool in the English teaching. Thirdly, this study is to find out the challenges faced by the English Language teachers in using computer and its technology as teaching tool in their English teaching. By looking at the frequency of usage, usefulness, the nature of integration and factors that hinder the English Language teachers from integrating computer and its technology as teaching tool, teachers’ readiness is discuss by using the Technology Acceptance Model (TAM) and the Technology Readiness Index (TRI). A questionnaire consisting of three sections that was based on the research questions was distributed to the English and MUET teachers. The data collected was analysed using SPSS Version 17. The findings were described using descriptive statistics and tabulated. The findings of the study show that teachers have positive views about using use computer and its technology in their language teaching. However, based on their actual frequency of usage and practices, the teachers do not actually often use computer and its technology in their teaching tool and they lack of ICT expertise to do so. With that, it can be concluded that English teachers in the Division are not ready for integrate computer and its technology in the teaching. Hence, training and technical support are recommendable to for these teachers.